Language in Language Evolution Research - Slawomir Wacewicz; Przemyslaw Zywiczynski; Stefan Hartmann; Michael Pleyer; Antonio Benítez-Burraco (Biolinguistics, 2021)
Many controversies in language evolution research derive from the fact that language is itself a natural language word, which makes the underlying concept fuzzy and cumbersome, and a common perception is that progress in language evolution research is hindered because researchers do not ‘talk about the same thing’. In this article, we claim that agreement on a single, top-down definition of language is not a sine qua non for good and productive research in the field of language evolution. First, we use the example of the notion FLN (‘faculty of language in the narrow sense’) to demonstrate how the specific wording of an important top-down definition of (the faculty of) language can—surprisingly—be inconsequential to actual research practice. We then review four approaches to language evolution that we estimate to be particularly influential in the last decade. We show how their breadth precludes a single common conceptualization of language but instead leads to a family resemblance pattern, which underwrites fruitful communication between these approaches, leading to cross-fertilisation and synergies.